2011
DOI: 10.5402/2011/514323
|View full text |Cite
|
Sign up to set email alerts
|

To Explore the Experiences of Women on Reasons in Initiating and Maintaining Breastfeeding in Urban Area of Karachi, Pakistan: An Exploratory Study

Abstract: This is an exploratory study that explores the experiences of lactating women in initiating, continuing, or discontinuing breastfeeding in an urban area of Karachi, Pakistan. Objectives. To explore the experiences of lactating women and to understand their support and hindering mechanisms in initiating and maintaining breastfeeding. Methods. This is an exploratory design assisting in exploring the participant's experiences of initiating and maintaining breastfeeding to better understand their world. Purposive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
(19 reference statements)
1
15
0
Order By: Relevance
“…Mother's health-related factors such as being unconscious after delivery[ 21 22 ] and fatigue[ 23 ] have been cited as potential factors in delaying breastfeeding. In our study, the reasons for delay in initiation of breastfeeding were mainly no milk (6.92%), mother having pain (6.37%), baby slept (1.93%), mother was in labor room (14.13%), baby did not accept (3%), and mother tired and slept (2.77%).…”
Section: Discussionmentioning
confidence: 99%
“…Mother's health-related factors such as being unconscious after delivery[ 21 22 ] and fatigue[ 23 ] have been cited as potential factors in delaying breastfeeding. In our study, the reasons for delay in initiation of breastfeeding were mainly no milk (6.92%), mother having pain (6.37%), baby slept (1.93%), mother was in labor room (14.13%), baby did not accept (3%), and mother tired and slept (2.77%).…”
Section: Discussionmentioning
confidence: 99%
“…We were worried because she was small when she was born. She would cry every thirty minutes for me but then didn't like me going near her, she just got frustrated (Bangladeshi mother, aged [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Barriers To Breastfeeding Physical Barriersmentioning
confidence: 99%
“…It is the perfect food that contains all the well-adjusted nutritious elements, for the new born. It is a type of nutrition that gives the same food to all the babies across the globe irrespective of socio-economic boundaries [1]. Research has revealed the important developmental, psychological, environmental, social, nutritional, immunological, and economical benefits of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…Research has revealed the important developmental, psychological, environmental, social, nutritional, immunological, and economical benefits of breastfeeding. It guards babies from acute respiratory infections and diarrhoea, reduces neonatal mortality, enhances response to vaccinations, and boosts their immune systems [1]. Likewise, many researches have mentioned the motherly health advantages of breastfeeding, such as more rapid uterine involution, decreased postnatal bleeding, reduce weight quickly, and less chances of breast and ovarian cancer [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation